Families Parenting Adolescents With Substance Abuse—Recovering the Mother's Voice: A Narrative Literature Review. (November 2014) - Smith, Jackie M.; Estefan, Andrew
Alcohol and substance dependency are complex, problematic phenomena, which are growing worldwide. In particular, drug use and abuse among young people is a significant concern. Although addiction presents as a problem of dependent individuals, families are also profoundly affected by the family member's addiction. In this narrative literature review, we review published research from 1937 to 2014 to capture a narrative and historical perspective of addiction and family. We condense and analyze the experiences of parents with alcohol- and drug-dependent children, to emphasize the need for a more specific, in-depth exploration of mothers' experiences. Such exploration may advance nurses' understandings of individual, familial, and social complexities of parenting an addicted child.